2022
DOI: 10.1093/ofid/ofac340
|View full text |Cite
|
Sign up to set email alerts
|

Stopping Oral Polio Vaccine (OPV) After Defeating Poliomyelitis in Low- and Middle-Income Countries: Harmful Unintended Consequences? Review of the Nonspecific Effects of OPV

Abstract: Background The live vaccines bacille Calmette-Guérin (BCG) and measles vaccine have beneficial non-specific effects (NSEs) reducing mortality more than can be explained by prevention of tuberculosis or measles infection. Live oral polio vaccine (OPV) will be stopped after polio eradication, we therefore reviewed the potential NSEs of OPV. Methods OPV has been provided in three contexts. First, co-administration of OPV and dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…In addition, we found that the booster dose of bOPV after 2sIPV-bOPV resulted in a 14.81% increase in seropositivity rates against poliovirus type 2. This result may indicate the possible cross-protection from bOPV, 17 which is consistent with research findings in Chilean infants. 18 But the heterotypic protection may not sufficiently raise immunity against poliovirus type 2 and has been observed to be short lasting.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we found that the booster dose of bOPV after 2sIPV-bOPV resulted in a 14.81% increase in seropositivity rates against poliovirus type 2. This result may indicate the possible cross-protection from bOPV, 17 which is consistent with research findings in Chilean infants. 18 But the heterotypic protection may not sufficiently raise immunity against poliovirus type 2 and has been observed to be short lasting.…”
Section: Discussionsupporting
confidence: 91%
“…10 As for the BCG vaccine, increasing evidence supports that OPV has beneficial non-specific effects. 11 A trial comparing BCG only versus BCG+OPV0 in neonates found that OPV0 reduced infant mortality by 32% (95% CI: 0% to 55%) before the next OPV campaign. 12 In the present trial, we aimed to test the impact of combining the WHO-recommended home visits with provision of the vaccines recommended at birth (BCG and OPV0).…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…OPV at birth (OPV0) is part of the strategy for eradicating polio 10. As for the BCG vaccine, increasing evidence supports that OPV has beneficial non-specific effects 11. A trial comparing BCG only versus BCG+OPV0 in neonates found that OPV0 reduced infant mortality by 32% (95% CI: 0% to 55%) before the next OPV campaign 12…”
Section: Introductionmentioning
confidence: 99%